1994
DOI: 10.1161/01.str.25.3.645
|View full text |Cite
|
Sign up to set email alerts
|

Changes in locomotor activity and passive avoidance task performance induced by cerebral ischemia in Mongolian gerbils.

Abstract: We investigated changes in locomotor activity, passive avoidance task performance, and hippocampal CA1 neurons induced by cerebral ischemia in Mongolian gerbils to examine the relation between these behavioral changes and CA1 neuronal damage. Spontaneous locomotor activity was measured using the open field method before and 1, 3, 7, 14, or 28 days after 1- to 5-minute occlusion of the bilateral common carotid arteries. Locomotor activity after the second episode of 5-minute ischemia was also measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Previous studies have shown that at the first day after operation, the ischemia-induced increase in locomotor activity is most prominent. It decreases over the following two days, and at 5 -7 days after operation there is no difference between the controls and ischemic animals (39,40). In this study, as we conducted the open field test 8 days after occlusion, the present result regarding locomotor activity conforms to these previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that at the first day after operation, the ischemia-induced increase in locomotor activity is most prominent. It decreases over the following two days, and at 5 -7 days after operation there is no difference between the controls and ischemic animals (39,40). In this study, as we conducted the open field test 8 days after occlusion, the present result regarding locomotor activity conforms to these previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we surmised that this behavioral change induced by cerebral ischemia does not correlate directly with hippocampal damage. This is because we found that when Mongolian gerbils were subjected to 5-min ischemia again 1 month after the initial 5-min ischemia, which had caused complete degeneration of hippocampal CA1 neurons, locomotor activity even 1 day after was again significantly increased (15). Feeney and coworkers (35) reported a single dose of damphetamine given 24 h following unilateral sensorimotor cortex ablation in the rat resulted in an enduring enhancement of motor recovery.…”
Section: Discussionmentioning
confidence: 75%
“…The preparations were stained with hematoxylin-eosin and cresyl-violet by an investigator blind to the experimental conditions. Ischemic neuronal damage was graded on a scale of 0 -3 as follows: 0 (-), normal neurons; 1 (+), a few neurons damaged (as few as one neuron damaged); 2 (++), many neurons damaged; and 3 (+++), the majority of neurons damaged (15).…”
Section: Histopathology Of the Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…Some spontaneous recovery of sensorimotor function has been demonstrated after brain ischemia . Following ischemic brain injury a locomotor hyperactivity has been noted for 7 days (Kuroiwa et al, 1991;Karasawa et al, 1994). Hyperactivity was directly connected with neuronal alterations in the ischemic hippocampus (Kuroiwa et al, 1991;Kiryk et al, 2011).…”
Section: Disabilities After Ischemiamentioning
confidence: 99%